An introduction to reliability and maintainability engineering - Ebeling, Charles E. (Waveland Press, 2010)
This book is about basic reliability models,data collection and empirical methods, reliability testing, reliability growth testing. Identifying failure and repair distributions will help all beginers who want to learn about Reliability and Maintainability Engineering.